‘Braun’: the first russian cotton cultivar with naturally colored fiber - R. K. Tuz; M. Sh. Asfandiiarova; L. P. Podolnaya (Труды по прикладной ботанике, генетике и селекции)
Background. Most commercial cotton cultivars have white fiber. Massive energy and water consumption during the production of fabrics from such fiber generates significant problems, so in recent decades more and more cotton cultivars with naturally colored fiber have appeared in the world. In addition to saving natural resources, such fiber has another advantage: it is lowallergenic. Such fiber is much more expensive on the world market.Materials and methods. The research material was cotton line 7C with light brown fiber, produced by individual selection from the hybrid combination Genetic 34 (Turkmenistan, late-maturity, brown fiber) × C2 8101-73 (k-8112, Albania, early-maturity, white fiber). This line was registered in the State Register for Selection Achievements as the cultivar ‘Braun’ in 2019. The authors of the cultivar were M. Sh. Asfandiyarova, L. P. Podolnaya, A. G. Dubovskaya, and R. K. Tuz. The selection achievement was patented (patent No. 10638). The research was conducted at the Caspian Research Institute of Arid Agriculture (now the Caspian Agrarian Federal Research Center of the RAS). 7C was compared to the white-fiber reference ‘AS-5’ for morphological and agronomic traits in 2013–2018 according to VIR’s guidelines.Results and conclusion. ANOVA analysis showed that cv. ‘Braun’ differed significantly from cv. ‘AS-5’ only in fiber length. However, the 5th type to which the fiber cv. ‘Braun’ belongs is used for the production of fabrics on a large scale. The cultivar’s yield of 2.5–3.0 t/ha is comparable to the reference. Variability of the values of the studied traits in cv. ‘Braun’ over the years was less than in the reference cultivar, attesting to its good adaptation to the Northern Caspian environments. The fiber’s natural color would make the products from such fiber notably more attractive. The estimated cost efficiency of its cultivation showed high profitability – up to 132%.